66.8k views
5 votes
What is the sum of 3x² - x -2 and x² + 2x - 1?

2 Answers

4 votes

Answer:

Explanation:

We can combine like terms in order to find this sum: 3x^2 + x^2 +2x -x -2-1= 2x^2 +x -3.

User Christos
by
4.8k points
4 votes
Line the equations up based on their common factor. Keep in mind the X has an understood 1 in front of it if there is no coefficient. So, X = (1)X. Add them up as shown in the picture.

3x^2 + (1)x^2 = 4x^2

-(1)x + 2x = (1)x

-2 + -1 = -3

Then put these in order based on their variable (same order as in the original equations) don’t include the understood one when writing your final equation as some teachers may take off points for it.

Final answer= 4x^2 + x - 3
What is the sum of 3x² - x -2 and x² + 2x - 1?-example-1
User Hayashi
by
5.1k points